Capacity building with academic partners - Nduah, Alex; Ogutu, Liz; Nzuki, Esther (2024)
AICCRA's collaboration with Kenyan universities has led to the co-development and operationalization of CSA relevant curricula and short courses, and the establishment of communities of practice with these partners and other stakeholders in the different areas of operation. These initiatives offer undergraduate (BSc) and postgraduate (MSc) programs, short courses, and hands-on demonstrations, equipping students, farmers, and policymakers with tools to address climate change impacts in the agriculture sector. Community engagement through demonstration farms and farmer training facilitated by the four universities has enhanced the access and adoption of CSA technologies, improving agricultural productivity and resilience among the small-scale farmers